The Implementation of Qur’anic Recitation (Tadarus) Habituation in Grade IV-A as a Means of Developing The Pancasila Student Profile - Miftahuddin Miftahuddin; Luthfia Febriana_Hediyanti (Jurnal Pendidikan Educandum, 2025)
This study aims to describe the implementation of Qur’an recitation habituation (tadarus Al-Qur’an) in class IV-A of MI Islamiyah Banjarmlati in shaping the Pancasila Student Profile. The background of this research is based on the importance of character formation through religious activities integrated with Pancasila values. The habituation of Qur’an recitation is considered an effective means of instilling the values of piety, cooperation, discipline, and responsibility among students. This study employs a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects included the class IV-A teacher, students, and the head of the madrasah. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings show that the Qur’an recitation habituation is carried out routinely every morning before lessons begin. Teachers serve as guides and motivators, while students demonstrate enthusiasm and active participation. This activity not only improves students’ Qur’an reading skills but also fosters religious attitudes, discipline, and a sense of responsibility. These values are in line with the dimensions of the Pancasila Student Profile. Thus, the habituation of Qur’an recitation contributes significantly to the holistic character formation of students within the madrasah environment.